Micro-structural studies of thermosonic Cu-Al bonding interface - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Jalar, Azman (2013)
Thermosonic Copper (Cu) wire interconnection has been under an extensive research and development with objective to replace expensive Gold (Au) wire material in the semiconductor industry. However, a reliability concern is raised due to void formation at the bonding interface of Copper wire-Aluminum bond pad (Cu-Al) after High Temperature Storage (HTS) annealing condition. It is believed that the Intermetallic Compound (IMC) layer growth and evolution lead to a volumetric shrinkage which in turn results in the void formation. This defect increases the electrical resistance of the micro-chip until a functionality failure occurs. The wire bonding and annealing conditions influence the development of the IMC at the bonding interface which is related to the bonding reliability. In this work, effects of bonding temperature and annealing toward the micro-structure and IMC growth at the bonding interface were evaluated using Scanning Transmission Electron Microscope equipped with Energy Dispersive X-ray facility. From the imaging results of as-bonded Cu wire samples, bonding temperature resulted in a rapid interdiffusion of Cu-Al. This resulted in a thicker and more uniform IMC formation at the bonding interface. After High Temperature Storage of 1000 hours, the consumption of the Al bond pad and diffusion of Cu into Si to form precipitates were observed. The chemical analysis shows multiple phases existed at the bonding interface especially for the sample synthesized with a lower bonding temperature. Moreover, the IMC of the annealed sample synthesized with higher bonding temperature developed in a superlattice-like structure.